COMMUNICATIVE AND PRAGMATIC PECULIARITIES OF THE SHORT NON- LITERARY TEXT (BASED ON THE MATERIALS OF SPANISH HOROSCOPES IN INTERNET RESOURCES) - Vasylieva Тetiana (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of horoscope texts posted on Spanish entertainment websites and on digital versions of the leading Spanish newspapers published in print format. Our research focuses on analyzing the features of Spanish horoscopes on different language levels, paying particular attention to their lexical, semantic, morphological and syntactic peculiarities. The relevance of the topic is been determined by the general focus of modern linguistics on studying texts of different genres of discourse, on the complex analysis of their lexical, semantic, structural and functional features from the perspective of anthropomorphism and pragmalinguistics. The analysis made it possible to characterize the horoscope as a kind of short non-literary text of the mass-media discourse. This text is creolized by its form and is informative by its function. Using the example of Spanish horoscope texts it was possible to determine the nature of communicative interaction between the addresser and the addressee and the pragmatic orientation, which is manifested in the author’ choice of verbal and non-verbal means of influencing the recipient. A detailed description of the lexical, semantic, morphological and syntactic features of the Spanish horoscopes and their pragmatic functions is given. The role of non-verbal means, which complement the texts, is been defined. The obtained results show, that the horoscope text has not only communicative and informative, but also persuasive, appealing, expressive and recreational functions and its communicative purpose is to influence the behavior of the addressee. ____________ References • Bogoderova, M. V. «Sovremennyj goroskop kak masmedijnyj vid teksta (na materiale nemeckogo jazyka).» Avtoref. diss. kand. filol. nauk, Ufa, 2010. • Chernjavskaja, V. E. Diskurs vlasti i vlast’ diskursa: problemy rechevogo vozdejstvija: ucheb. posobie, 2-e izd., ster. (Moskva: FLINTA: Nauka, 2012), 128, dostup http://znanium.com/catalog/ product/457226 • Martinell Gifre, Emma. «Anuari de filologia.» Estudios de lengua y literatura españolas 1 (1990): 57-64. • Montero Curiel, María Luisa. «Sobre la lengua de los horóscopos.» Anuario de estudios filológicos 16 (1993): 295-308 • Dakhil Diab, Mohamad. «Estudio en la traducción del lenguaje de los horóscopos en la prensa del idioma español al árabe.» Journal of the College of Languages 34 (2016): 42-67. • Valgina, N. S. Teorija teksta: Uchebnoe posobie (Moskva, Logos, 2004), 280. • Sorokin Ju. A., Tarasov E. S. «Kreolizovannye teksty i ih kommunikativnaja funkcija.» Optimizacija rechevogo vozdejstvija (Moskva, 1990). • Anisimova, E. E. Lingvistika teksta i mezhkul’turnaja kommunikacija: na materiale kreolizovannyh tekstov (Moskva, Academia, 2003), 128. • Chudinov, A. P. «Rossija v metaforicheskom zerkale: kognitivnoe issledovanie politicheskoj metafory (1991-2000).» Monografija (Ekaterinburg, 2001), 238. • Horóscopo mágico, доступ http:// www.horoscopo.com • Univisión: Show, Entretenimiento, Noticias, Deportes y Novelas доступу: http://www.univision.com • Horóscopo diario de 20 minutos, доступ http://www.20minutos.es • El País. El periódico global, доступ http://www.elpais.es • ABC Horóscopo, доступ http://www.horoscopo.ABC.es • 15. El Mundo. Horóscopo diario gratis, доступ http://www.elmundo.es/horoscopo • Clarín. Horóscopo de hoy, доступу: https://www.clarin.com/horoscopo • Candas 365 Noticias – Diario digital asturiano, доступ http:// www.candas365.es